Pre- and Postnatal Exposure to Low Dose Glufosinate Ammonium Induces Autism-Like Phenotypes in Mice - Laugeray, Anthony; Herzine, Ameziane; Perche, Olivier; Hébert, Betty; Aguillon-Naury, Marine; Richard, Olivier; Menuet, Arnaud; Mazaud-Guittot, Séverine; Lesné, Laurianne; Briault, Sylvain; Jegou, Bernard; Pichon, Jacques; et al. (Frontiers in Behavioral Neuroscience, 2014)
Glufosinate ammonium (GLA) is one of the most widely used herbicides in agriculture. As is the case for most pesticides, potential adverse effects of GLA have not been studied from the perspective of developmental neurotoxicity. Early pesticides exposure may weaken the basic structure of the developing brain and cause permanent changes leading to a wide range of lifelong effects on health and/or behavior. Here we addressed the developmental impact of GLA by exposing female mice to low dose GLA during both pre- and postnatal periods and analyzed potential developmental and behavioral changes of the offspring during infancy and adulthood. A neurobehavioral test battery revealed significant effects of GLA maternal exposure on early reflex development, pup communication, affiliative behaviors, and preference for social olfactory cues, but emotional reactivity and emotional memory remained unaltered. These behavioral alterations showed a striking resemblance to changes seen in animal models of Autistic Spectrum Disorders. At the brain level, GLA maternal exposure caused some increase in normalized brain weight of the offspring. In addition, reduced expression of Pten and Peg3 - two genes implicated in autism-like deficits – was observed in the brain of GLA-exposed pups at postnatal day 15. Our work thus provides new data on the link between perinatal exposure to the herbicide GLA and the onset of autism-like symptoms later in life. It also raises fundamental concerns about the ability of current safety testing to assess risks of pesticide exposure during critical developmental periods.